جماليات المكان الصور والوظائف: رواية "ساق البامبو" لسعود السنعوسي نموذجاً - عمران، علي أحمد (مركز رفاد للدراسات والأبحاث, 2019)
This study presents the aesthetics of the place in the Kuwaiti novel represented in the story of the leg of the bamboo. In this context, it is divided into four sections. The first section, entitled "aesthetics," focuses on the concept of aesthetics in language, morphology. The term "aesthetics" and "poeticism", and the relation of esthetics to the place. The second section, entitled "Place term", focuses on the linguistic meaning, the relation of place to time, and the distinction between two terms (space, place) (Photos of the place) comes to inspect the places enclosed in the novel leg Al Bamboo, the open spaces, and how to employ them in the statement of the confusion of the hero Issa and his pain, between the places in Kuwait and the Philippines. Finally comes the fourth section entitled (Functions of the aesthetics of the place) to focus on three basic functions, And his role in the novel, which is as follows: psychological function, the imaginary function, and the function of reporting, which are basic functions that branch to other secondary functions, and clearly shows the suffering of the protagonist Issa, and his great tragedies, and loss of his identity as a human. The conclusion summarizes the findings of the research on the aesthetics of the place in “the bamboo leg story” and functions.
يطرح هذا البحث جماليات المكان في الرواية الكويتية ممثلة في رواية ساق البامبو، وهي تنقسم-في هذا السياق -إلى أربعة أقسام: ويركز القسم الأول -المعنون ب (مصطلح الجماليات) على مفهوم الجماليات في اللغة، والصرف، والمعجم، وتاريخية المصطلح، والتفريق بين مصطلح (الجماليات) و(الشعرية)، وعلاقة الجماليات بالمكان، ثم يأتي القسم الثاني المعنون ب (مصطلح المكان) ليركز على المعنى اللغوي، وعلاقة المكان بالزمان، والتفريق بين ثلاثة من المصطلحات (المكان، والحيز، والفضاء)، أما القسم الثالث المعنون ب ( صور المكان) فيأتي لفحص الأمكنة المغلقة في رواية "ساق البامبو"، والأمكنة المفتوحة، وكيفية توظيفها في بيان حيرة البطل عيسى، وألمه، وضياعه، وتيهه، بين الأمكنة في (الكويت، والفلبين). وأخيرا يأتي القسم الرابع المعنون ب (وظائف المكان) ليركز على ثلاث وظائف أساسية انتابت البطل عيسى وأدت إلى تيهه وضياعه في الرواية، وهي على النحو الآتي: الوظيفة النفسية، والوظيفة التخيلية، والوظيفة الإبلاغية، وهي وظائف أساسية تتفع إلى وظائف ثانوية أخرى، وتبين بجلاء معاناة بطل الرواية عيسى، ومأساته العظمي، وضياع هويته كإنسان. وتلخص الخاتمة ما وصل إليه البحث من النتائج حول جماليات المكان: صوره، ووظائفه في رواية "ساق البامبو"
Keywords: الأدب العربي -- السرد الروائي -- الأساليب البلاغية -- النقد الأدبي -- السنعوسي، سعود